Night and day egestion rates of the copepod Centropages typicus in the presence and the absence of the predator Meganyctiphanes norvegica [Dataset] ... - Olivares, Manuel; Tiselius, Peter; Calbet, Albert; Saiz, Enric (CSIC - Instituto de Ciencias del Mar (ICM), 2020)
Predators can induce changes in the diel activity patterns of marine copepods. Besides vertical migration, diel feeding rhythms have been suggested as an antipredator phenotypic response. We conducted experiments to assess the non-lethal direct effects of the predator Meganyctiphanes norvegica (northern krill) on the diel feeding patterns of the calanoid copepod Centropages typicus. We also analysed the inﬂuence of seasonal photoperiod and prey availability on the intensity of copepod feeding rhythms. We did not detect any large effect of krill presence on the diel feeding behaviour of copepods, either in day-night differences or total daily ingestions. Seasonal photoperiod and prey availability, however, signiﬁcantly affected the magnitude of copepod feeding cycles, with larger diel differences in shorter days and at lower prey concentrations. Therefore, the role of non-lethal direct effects of predators on the diel feeding activity of marine copepods remain debatable and might not be as relevant as in ... : Number of experiment, date of experiment, temperature, bottle volume, prey species, prey species AphiaID, copepod species, copepod species AphiaID, predator species, predator species AphiaID, day/night, predator/no predator, prey concentration, prey size, number of copepods per bottle, copepod size, number of predators per bottle, predator size, incubation time, number of copepod faecal pellets, faecal pellet volume ...